Analysis of the Implementation of Public Service Standards at the District Level - Sholichah, Anis; Muin, Sri Adrianti; Mujahid, Mujahid (Journal of Management and Administration Provision, 2025)
Service Standards are benchmarks used as guidelines for service delivery and as references for assessing service quality, representing the obligation and commitment of service providers to the community in delivering quality, fast, easy, affordable, and measurable services. This study aims to determine and analyze the implementation of public service standards in Penajam Sub-District, Penajam Paser Utara District. The research adopts a qualitative descriptive approach method. Data in this study consist of primary and secondary data, which were analyzed qualitatively, leading to drawn conclusions. Primary data were obtained through in-depth interviews with informants at the Penajam Sub-District Office, including the Sub-District Head, General Affairs Subsection Head, Section Heads, Sub-District Employees/Staff, and service users from the community. The findings of the research are as follows: 1) The overall implementation of public service standards in Penajam Sub-District is reasonably good and sufficiently satisfying to the community. However, there is still a need for improvement and enhancement in the quality of public service implementation; 2) The preparation, establishment, and implementation of Service Standards in Penajam Sub-District have adhered to the principles outlined in Regulation of the Minister of Administrative Reform and Bureaucratic Reform Number 15 of 2014, including simplicity, accountability, sustainability, and fairness. However, they have not yet fully incorporated participatory and transparent elements; 3) There are several types of services with detailed per-component service standards that have not been established in the Decree of the Penajam Sub-District Head, Penajam Paser Utara District Number: 060/129/Kec.PNJ-Umum/XI/2023 regarding the Establishment of Service Standards in Penajam Sub-District; 4) Subsequent socialization efforts related to the established Penajam Sub-District Service Standards have not been conducted, thus affecting the understanding of service officers regarding public service implementation; 5) Publication efforts concerning Penajam Sub-District Service Standards have not been undertaken through electronic or non-electronic media.